Consumer Dispute Settlement: A Comparative Study on Indonesian and Malaysian Law - Norma Sari (Faculty of Law, Universitas Padjadjaran, 2018)
AbstractConsumer dispute settlement becomes an important instrument for protecting consumers. This study aims to analyze: (i) the urgency of consumer dispute settlement body and small claim mechanism; (ii) the comparison of consumer dispute settlement law in Indonesia and Malaysia; (iii) a lesson from Malaysia concerning small claim court. This research was conducted as a library research. The results show that urgency of consumer dispute settlement body and small claim mechanism are to guarantee ultimate consumer interest. Comparing the consumer dispute settlement law in Indonesia and Malaysia, each institution and mechanism has advantages and disadvantages to consider for betterment in the future. Consumer Dispute Agency is a middle way or a combination of SCC system and specific dispute resolution body. However, Indonesia needs to reiterate the existing Consumer Protection Act regarding the duty and authority of Consumer Dispute Settlement Agency. There is authority overlap with other agencies needed to be addressed.AbstrakPenyelesaian sengketa konsumen menjadi instrumen penting dalam perlindungan konsumen. Penelitian ini bertujuan menganalisis: (i) urgensi badan penyelesaian sengketa konsumen dan mekanisme penyelesaian tuntutan secara sederhana; (ii) perbandingan badan penyelesaian sengketa konsumen di Indonesia dengan Malaysia; (iii) pelajaran dari malaysia tentang peradilan tuntutan sederhana bagi konsumen. Hasil penelitian menunjukkan urgensi badan penyelesaian sengketa konsumen dan mekanisme klaim sederhana adalah untuk menjamin kepentingan terakhir konsumen. Membandingkan hukum penyelesaian sengketa konsumen di Indonesia dan Malaysia, masing-masing institusi dan mekanisme memiliki kelebihan dan kekurangan yang perlu dipertimbangkan untuk perbaikan masa depan. BPSK adalah jalan tengah atau kombinasi dari sistem Small Claim Court dan badan penyelesaian sengketa yang spesifik. Namun, Indonesia perlu meninjau ulang Undang-Undang Perlindungan Konsumen yang ada mengenai tugas dan wewenang BPSK. Ada otoritas tumpang tindih dengan badan lain yang perlu diatasiDOI: https://doi.org/10.22304/pjih.v5n1.a6